2022
DOI: 10.3390/ani12192710
|View full text |Cite
|
Sign up to set email alerts
|

gga-miR-449b-5p Regulates Steroid Hormone Synthesis in Laying Hen Ovarian Granulosa Cells by Targeting the IGF2BP3 Gene

Abstract: MiRNAs have been found to be involved in the regulation of ovarian function as important post-transcriptional regulators, including regulators of follicular development, steroidogenesis, cell atresia, and even the development of ovarian cancer. In this study, we evaluated the regulatory role of gga-miR-449b-5p in follicular growth and steroid synthesis in ovarian granulosa cells (GCs) of laying hens through qRT‒PCR, ELISAs, western blotting and dual-luciferase reporter assays, which have been described in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Like in most animals, the egg production of laying hens is mainly controlled by the hypothalamic-pituitary-ovarian axis ( HPG ) ( Du et al, 2020 a). Following the elucidation of the endocrine mechanism of HPG, granulosa cells have been the focus of many studies on the mechanism of follicle growth and survival ( Wu et al, 2022 ). In vivo and in vitro experiments have shown that factors secreted by granulosa cells, including gonadal steroids, growth factors, and cytokines, are essential for granulosa cell survival and eventual follicle growth.…”
Section: Introductionmentioning
confidence: 99%
“…Like in most animals, the egg production of laying hens is mainly controlled by the hypothalamic-pituitary-ovarian axis ( HPG ) ( Du et al, 2020 a). Following the elucidation of the endocrine mechanism of HPG, granulosa cells have been the focus of many studies on the mechanism of follicle growth and survival ( Wu et al, 2022 ). In vivo and in vitro experiments have shown that factors secreted by granulosa cells, including gonadal steroids, growth factors, and cytokines, are essential for granulosa cell survival and eventual follicle growth.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified rigosertib as a potent small molecule that can suppress tumorigenesis by downregulating IGF2BP3 [ 41 ]. Non-coding RNAs such as miR-486 [ 42 ] and gga-miR-449b-5p [ 43 ] are also attractive alternative approaches to target IGF2BP3. More detailed preclinical studies are required before these drugs can be considered a concrete possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In hens, after synthesized in granulosa cells of the hierarchical follicle, P4 converts to E2 in theca cells catalysed by aromatase enzymes (Jing et al, 2018). E2 and P4 have been proved to be involved in the regulation of chicken ovarian function, as important regulators of follicle development and maturation, cell proliferation and differentiation (Du et al, 2020; Li et al, 2022; Wu et al, 2022). In this study, P4 biosynthesis in granulosa cells increased significantly during the follicle selection (SYF to F5), and it was incremental during the preovulatory hierarchical development.…”
Section: Discussionmentioning
confidence: 99%